2021
DOI: 10.1007/s10826-021-02000-7
|View full text |Cite
|
Sign up to set email alerts
|

Child Welfare Services Response to COVID-19: Addressing Face-to-Face Contacts

Abstract: During the onset of the COVID-19 pandemic, child welfare case managers faced contradictions in their responsibility to make regular in-person contact with children and families to promote safety, permanency, and well-being while following public health directives to avoid social contact in order to curb COVID-19 infections. In response, federal guidance was issued regarding the use of technology to maintain mandated contacts with children in foster care. States had to make decisions about how to handle other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…During the onset of the COVID‐19 pandemic, child welfare service providers faced contradictions in their responsibility to make regular in‐person contact with children and families to promote safety, permanence and well‐being while following public health directives to avoid social contact in order to curb COVID‐19 infections. In response, federal guidance was issued regarding the use of technology to maintain mandated contact with children in foster care (Seay & McRell, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the onset of the COVID‐19 pandemic, child welfare service providers faced contradictions in their responsibility to make regular in‐person contact with children and families to promote safety, permanence and well‐being while following public health directives to avoid social contact in order to curb COVID‐19 infections. In response, federal guidance was issued regarding the use of technology to maintain mandated contact with children in foster care (Seay & McRell, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the onset of the COVID-19 pandemic, child welfare service providers faced contradictions in their responsibility to make regular inperson contact with children and families to promote safety, permanence and well-being while following public health directives to avoid social contact in order to curb COVID-19 infections. In response, federal guidance was issued regarding the use of technology to maintain mandated contact with children in foster care(Seay & McRell, 2021).During this difficult time, vulnerable families are also at risk of losing access to services or experiencing a reduction in quality as providers attempt to move services to a virtual format. In the early days of the pandemic, efforts to reduce the viral spread of COVID-19 involved limiting face-to-face contact with human service professionals, including education providers and healthcare providers.Many education systems (including daycares, preschools, elementary, middle and high schools, community colleges and universities) have transitioned from classroom instruction to virtual homeschool instruction (Van Lancker & Parolin, 2020).…”
mentioning
confidence: 99%
“…Australian parents with children in OOHC have also reported the distressing nature of reduced or no contact (Fogarty et al, 2022). Yet there is also evidence of efforts being made by service providers to implement supportive practices and increase communication to vulnerable families and children (Seay & McRell, 2021; Wilke et al, 2020). An exploratory study exploring birth family contact found virtual visits can be effective when well‐supported by caseworkers and may offer important ongoing opportunities for family connections post the COVID‐19 restrictions, to support connections when distance, incarceration or transport issues are present (Langley et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Child welfare professionals were required to pivot from a face-to-face practice modality to working remotely and communicating with clients through virtual approaches -contributing a new set of stresses. Systemwide shortcomings associated with technology, infrastructure, and the need for improved training became increasingly evident (Loria et al, 2021;Schwab-Reese, Drury, Allan, & Matz, 2020;Seay & McRell, 2021). Concerns about the pandemic's impact on child welfare practice (e.g., increased levels of maltreatment and placements, etc.)…”
Section: Covid-19 and Child Welfarementioning
confidence: 99%